IDENTIFIKASI KETERDAPATAN SEBARAN PASIR ZIRKON DI KECAMATAN KENDAWANGAN KABUPATEN KETAPANG - Flaminggo Gingga; Desyana Ghafarunnisa; Muh Anhar; Sy. Indra Septiansyah (JURNAL SIMETRIK, 2026)
Zircon sand (Zr) is widely associated with alluvial deposits, particularly in Ketapang Regency. Despite the considerable zircon resource potential, information regarding its occurrence and spatial distribution at a local scale remains limited. Identifying zircon sand occurrence is therefore essential as an initial step in evaluating and developing Zr resource potential. This study aims to determine the occurrence and analyze the spatial distribution of zircon sand in Kendawangan District, Ketapang Regency. Geologically, the study area is predominantly composed of swampy mud deposits (Qs). The geomorphology consists of two main landform units: Alluvial Plain Unit (Al) covering approximately 65% and Swamp Plain Unit (Dr) covering 35%. A total of 24 boreholes were drilled on a 150 m × 150 m grid over an area of 200 hectares. The subsurface is classified into three layers (A, B, and C), with 1 kg samples collected from each layer. Spatial distribution mapping of Zr was conducted using QGIS with the Inverse Distance Weighting interpolation method. The Zr grade distribution in Layer A is dominated by low to moderate values (6–28 mg), relatively uniform across the study area, indicating low to moderate mineralization potential. In Layer B, Zr grades are predominantly high (39–62 mg) and widely distributed, particularly in the central to southern parts, suggesting higher mineralization potential and better prospectivity for exploration. Layer C exhibits more heterogeneous distribution, with moderate to high grades (28–50 mg) covering most of the area, indicating a fairly favorable mineralization potential. Keywords: Alluvial, Grade, Inverse Distance Weighting, Ketapang Regency, Layer, Spatial, Zircon Sand,